Korzyści finansowe z tytułu podatku VAT w wybranych gospodarstwach rolnych dokonujących inwestycji - Ginter, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of the article was to show the financial benefits of the lump-sum tax resignation of Value Added Tax in farms, which are progressing by investment in modern agricultural equipment. Ine article was proved that polish farmers are awareness of accounting system for the value added tax. To analise the problem the experiment was carried out in sixteen farms, located on Mazovia woivodeship, in three districts, siedlecki district, sokołowski district and węgrowski district. Nine farms were taxed on bases rules and sewen were lump-sum tax payers. The data were collected